How Motivation, Training, and Communication Improve Employee Morale - I Gede Agus Wahyu Nurjaya; Made Setena (International Journal of Islamic Business and Management Review, 2026)
This research highlights the importance of employee morale in facing competition and organizational efficiency demands in the era of globalization. Perumda Pasar Sewakadarma Denpasar City, as a traditional market manager, is experiencing signs of declining employee morale, as evidenced by an average attendance rate of 3.65% in 2024, which is categorized as high. Therefore, it is important to investigate the underlying issues that contribute to this issue. This study aims to analyze and explain the impact of motivation, training, and communication on employee morale, both collectively and individually. The study used a quantitative methodology using survey techniques, with a total of 679 workers asked to fill out the survey, and 87 of them were randomly selected. A variety of statistical tests, including multiple linear regression, t-test, F-test, and determination coefficient, were used to analyze the data. According to the study's findings, there was a positive and significant relationship between motivation, training, and morale (Sig. = 0.028), and training, communication, and enthusiasm all had a positive and significant influence (Sig. <0.001). Simultaneously, inspiration, instruction, and communication had a significant effect on morale (F = 58.375; Sig. < 0.001), with the model's ability to explain the variation in morale of 67.8% (R² = 0.678). These findings confirm that increased employee morale can be encouraged through strengthening motivation, effective training, and clear and open organizational communication.